Immunogenicity of the biosimilar CT-P13 infliximab or the original infliximab in Iraqi patients with Ankylosing spondylitis does not correlate with their demographic characteristics - Mohammed M. Kamil; Mohammed Abdul- Hassan Jabarah; Nizar A.l. Jasim (مجلة كلية الطب, 2023)
Background: Ankylosing spondylitis is a rare disease affecting people with hereditary factors. Its treatment includes life style modification and use of drugs such as the biologic agent infliximab or its biosimilar, CT-P13 infliximab. Despite their therapeutic usefulness, these agents are associated with a number of serious adverse effects such as immunogenicity.